The novel use of pop‐off satellite tags (PSATs) to investigate the migratory behaviour of European sea bass Dicentrarchus labrax. Issue 5 (1st April 2018) - O'Neill, R.; Ó Maoiléidigh, N.; McGinnity, P.; Bond, N.; Culloty, S.
Abstract : A total of 12 adult European sea bass Dicentrarchus labrax were tagged with pop‐off satellite archival tags (PSAT) in Irish coastal waters and in offshore waters in the north‐east Celtic Sea between 2015 and 2016. Archived data were successfully recovered from five of the 12 tags deployed, three from fish released in inshore Irish waters and two from fish released offshore in the eastern Celtic Sea. All three fish tagged in inshore waters were found to undertake migrations into the open ocean coinciding with the spawning period. These fish also exhibited fidelity to inshore sites post‐migration, returning to the same general location (within c . 73 km, which is roughly the predicted mean accuracy of the method) of their original release site. Although the number of tracks obtained here was limited, some degree of aggregation between inshore and offshore tagged fish in the eastern Celtic Sea was noted during the expected spawning period suggesting PSATs can provide new information on specific spawning locations of European sea bass.